Resonance structure of τ-→Κ-π+π -ντ decays - Asner, D; Eppich, A; Gronberg, J; Hill, T; Lange, D; Morrison, R; Briere, R; Behrens, B; Ford, W; Gritsan, A; Roy, J; Smith, J; et al. (2000)
Using a sample of 4.7 fb-1 integrated luminosity accumulated with the CLEO II detector at the Cornell Electron Storage Ring (CESR), we investigate the mass spectrum and resonant structure in τ- →Κ-π+π-ντ decays. We measure the relative fractions of Κ1(1270) and Κ1(1400) resonances in these decays, as well as the Κ1 masses and widths. Our fitted Κ1 resonances are somewhat broader than previous hadroproduction measurements, and in agreement with recent CERN LEP results from tau decay. The larger central value of our measured width supports models which attribute the small τ-→Κ-π+π -ντ branching fraction to larger Κ1 widths than are presently tabulated. We also determine the Κa-Κb mixing angle θΚ. ©2000 The American Physical Society.